2017
DOI: 10.3389/fmed.2017.00035
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Radionuclide Imaging in Rodents: A Review of Methods, Results, and Factors at Play

Abstract: The interest around small-animal cardiac radionuclide imaging is growing as rodent models can be manipulated to allow the simulation of human diseases. In addition to new radiopharmaceuticals testing, often researchers apply well-established probes to animal models, to follow the evolution of the target disease. This reverse translation of standard radiopharmaceuticals to rodent models is complicated by technical shortcomings and by obvious differences between human and rodent cardiac physiology. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…Clinically established imaging of vascular pathologies includes structural imaging, such as echocardiography and cardiac MRI ( 27 ), contrast-enhanced ultrasound imaging to measure microvascular blood flow and blood volume ( 23 ), as well as targeted dual-isotope PET viability studies with 13 N-ammonia and 18 F-FDG, to measure myocardial perfusion and viability ( 20 , 24 , 26 , 27 ). Other examples of clinically targeted vascular imaging include imaging of vascular permeability of carotid arteries ( 38 , 110 ), imaging of vessel inflammation by iron oxide nanoparticles ( 59 ), PET/MRI to detect α v β 3 integrin activation and predict outcome in infarct patients ( 89 ) and magnetization transfer MRI for fibrosis evaluation ( 111 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinically established imaging of vascular pathologies includes structural imaging, such as echocardiography and cardiac MRI ( 27 ), contrast-enhanced ultrasound imaging to measure microvascular blood flow and blood volume ( 23 ), as well as targeted dual-isotope PET viability studies with 13 N-ammonia and 18 F-FDG, to measure myocardial perfusion and viability ( 20 , 24 , 26 , 27 ). Other examples of clinically targeted vascular imaging include imaging of vascular permeability of carotid arteries ( 38 , 110 ), imaging of vessel inflammation by iron oxide nanoparticles ( 59 ), PET/MRI to detect α v β 3 integrin activation and predict outcome in infarct patients ( 89 ) and magnetization transfer MRI for fibrosis evaluation ( 111 ).…”
Section: Discussionmentioning
confidence: 99%
“…An in vivo mouse study using a clinical SPECT system showed perfect estimation of perfusion defects and non-invasive quantitation of myocardial infarct size (25). Perfusion imaging using either gated blood pool SPECT with 99m Tc-sestamibi or SPECT with labeled erythrocytes using 99m Tc-pertechnetate has low resolution and is mainly used to non-invasively quantify myocardial infarct size (26). Previous studies have used 13 Nammonia for detection of myocardial perfusion, as well as radiolabeled fluorodeoxyglucose (FDG), a glucose tracer, for detection of myocardial glucose metabolism, viability and left ventricular function (26).…”
Section: Multi-scale Imaging Of Heart and Large Vessels Vessel Density And Perfusionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review article ( 16 ) has identified WKY and Sprague–Dawley (SD) rats as commonly used strains in both cardiac PET and SPECT imaging studies. Previous studies have computed and measured cerebral K i in SD rats ( 1 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…The SYN1 tracer has several advantages when compared to other clinically used compounds, including the half-life of the radioisotope ( 18 F) ensuring stable signal and safety to the patients when compared with other isotopes in use (incl. 201 Tl, 82 Rb, 13 N) [8][9][10][11]. SYN1 combines a reasonable half-life of 110 min and the positrons of the lowest energy.…”
Section: Introductionmentioning
confidence: 99%